Comparison of efficacy and safety of intravenous iron sucrose and intramuscular iron sorbitol therapy in patients with anemia during pregnancy in a developing country - Harsha Shailesh Gaikwad (Asian Journal of Medical Sciences, 2017)
Background: Iron deficiency anemia due to poor nutritionis estimated to affect nearly two thirds ofall pregnant women in developing countriesparticularly in India. The responsible constellation of factors producing iron deficiency anemia generally precede the pregnancy, which includedeficient diet in iron content coupled with menstrual losses,generally a rapid succession of pregnancies and inadequate supplemental iron are a few to be blamed for a high incidence of anemia in such population.